Nigeria : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2021)
The Nigerian economy is at a critical juncture. A weak pre-crisis economy characterized by falling per capita income, double-digit inflation, significant governance vulnerabilities and limited buffers, is grappling with multiple shocks from the COVID-19 pandemic. Real output is projected to contract by 3.2 percent in 2020, with a weak recovery likely to keep per capita income stagnant and no higher than the 2010 level in the medium term. Policy adjustment and reforms are urgently needed to navigate this crisis and change the long-running lackluster course.